THE FORMULATION OF WHEAT FLOUR AND BREADFRUIT (Arthocarpus altilis) PASTE ON PHYSICOCHEMICAL PROPERTIES OF DONUTS - Khatimah, Asri Hudailmi (Fakultas Pertanian Universitas Tanjungpura, 2019)
The diversification of donut making from wheat flour and breadfruit paste formulations has been carried out. This study was aimed to determine the best formulations of wheat flour and breadfruit paste on properties of physicochemical. The experiment was designed using Rendomized Block Design with one factor formulation of wheat flour : breadfruit paste (100:0 g, 90:10 g, 80:20 g, 70:30 g, 60:40 g, 50:50 g). The best result of the study showed formulation of wheat flour and breadfruit paste 60% : 40% which is moisture content (26.47%), ash content (1.85%), fat content (14.33%), protein content (7.29%), carbohydrate content (50.89%), and improving degree (12.57%).